(untitled) (European Journal of Economics, Finance and Business Development, 2025)
Effective project management techniques are critical to the success and long-term sustainability of organizations across various sectors. In this article, the project management methodologies adopted by multinational companies in Uzbekistan are explored and how these methods can be adapted to the local environment. From a study of the methodologies adopted by multinational companies, the article reveals the strengths of established frameworks such as Agile, Waterfall, and Hybrid models. It also touches upon the particular issues in the Uzbek business climate, including cultural aspects, regulation, and the need for professional project managers. According to the study, by implementing the best global project management practices and local expertise, Uzbek organizations can enhance operational efficiency, enhance the amount of results achieved, and ultimately drive economic progress in the country.